2019
DOI: 10.4085/1062-6050-397-18
|View full text |Cite
|
Sign up to set email alerts
|

Sport Specialization and Fitness and Functional Task Performance Among Youth Competitive Gymnasts

Abstract: Context Gymnastics trains fundamental movement skills but has high rates of early sport specialization. Early specialization is associated with increased injury risk. Gymnasts devote time to developing technical skill, but whether specialization status influences performance is unknown. Objective To describe the participation and specialization characteristics of youth club gymnastics participants and determine whether the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 24 publications
0
67
1
Order By: Relevance
“…7,28,31,33 Of the remaining studies, seven showed some measures of movement competence were worse in high specialised athletes, but other measures did not differ. 3,24,25,27,30,32,34 Some differences were evident in measures of jump landing mechanics and performance, LESS, muscular strength and endurance, Y-balance, aerobic endurance, and flexibility.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,28,31,33 Of the remaining studies, seven showed some measures of movement competence were worse in high specialised athletes, but other measures did not differ. 3,24,25,27,30,32,34 Some differences were evident in measures of jump landing mechanics and performance, LESS, muscular strength and endurance, Y-balance, aerobic endurance, and flexibility.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…[32][33][34] The majority involved early to mid-adolescent participants (age range 12-16), 3,7,24,27,28,[31][32][33] with three studies including younger participants (as young as 6 years in one study). 25,30,34 Two retrospective studies included adults (aged [19][20][21][22][23][24][25], who were grouped based on high school sport participation. 26,29 Methods used to classify specialisation…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Injuries detrimentally affect the final ranking position with higher availability rates associated with better outcomes on athletic success (Drew et al, 2017). Despite not being very healthy, observational studies show that between 23.5% and 43.5% of gymnasts participate in training and competitions when they are injured (Root et al, 2019). Thus, the resultant increase in injuries must be taken into matter when determining training schedules for elite gymnasts.…”
Section: Discussionmentioning
confidence: 99%
“…Both RG and AG are international sports, recognized by the Italian Federation of Gymnastics (FIG). Both these two forms of gymnastics share many similar attributes but differ in terms of events, rules, and style [9]. For females, AG events include performances on different equipment (e.g., vault, uneven bars, balance beam, and floor), while RG events are all performed on the same equipment-a padded floor, that can vary according to the specific support utilized (e.g.…”
Section: Introductionmentioning
confidence: 99%